Effects of varying pH on membrane distillation bioreactor operation - Wong, Qian Ying. (2011)
Varying operational parameters can affect the Membrane Distillation Bioreactor (MDBR) retentate characteristics and hence, the permeate characteristics. The literature review covers the effects of the retentate characteristics on membrane fouling. Since the feed-biomass characteristics will affect the membrane process (fouling and flux), a literature review on the effects of varying operational parameters which include organic loading, Hydraulic Retention Time (HRT), Solid Retention Time (SRT) and pH on retentate organic carbon concentration, biomass concentration and Extracellular Polymeric Substances (EPS) production. The scope of this study is restricted to determining the effects of pH control on characteristics of permeate and retentate. The MDBR was operated with and without pH control. Acclimatized study was carried out to verify the results observed in the MDBR. From this study, it was found that lowering of the system pH could improve the biological and nutrient removal. The results show a lower TOC concentration and lower pH reduces the formation of ammonia gas as the pKa of ammonium is 9.27. Hence, it would improve the quality of permeate. However, higher amount of bound EPS was found at lower pH. Therefore, bound EPS is more critical than loose EPS in membrane fouling and flux decline.